Design and experiment of centralized pneumatic deep precision fertilization device for rice transplanter - Zha, Xiantao; Zhang, Guozhong; Zhang, Shijie; Hou, Qunxi; Wang, Yang; Zhou, Yong (International Journal of Agricultural and Biological Engineering, 2020)
To improve the precision of deep fertilization of paddy fields, a six-row centralized pneumatic deep precision fertilization device for a rice transplanter was designed. This device included a spiral fertilizer distribution system, centralized pneumatic fertilizer delivery system, an opener system, and a fertilization control system. The centralized airflow distribution method was used in the fertilizer delivery system to ensure that the airflow in each fertilizer pipe was evenly distributed. The rotational speeds of the power take-off (PTO) and fertilizer shaft were measured synchronously using photoelectric sensors and matched proportionately in real-time using PID closed-loop control algorithms to achieve precise fertilization rates at each working speed of the rice transplanter. There were two key considerations in the design of the control system to ensure precise fertilization. Firstly, a photoelectric sensor was used to measure the speed of the PTO; the high rotational speed of the PTO could provide a high signal frequency and improve the precision of the measurement of the transplanter’s working speed. Secondly, the fertilizer shaft speed measurement subprogram was set to sleep for a short period to reduce the vibration caused by the engine. During the tests of pneumatic fertilizer delivery system, single-factor tests on airflow distribution methods were conducted. The results showed that the coefficient of variation of the airflow speed for the centralized airflow distribution method was 1.67%, which was the least among the coefficients of the three distribution methods. In the bench tests, the rotational speeds of the fertilizer shaft were set at 10 r/min, 20 r/min, 30 r/min, and 40 r/min. The maximum coefficient of variation of the fertilization consistency in different rows was 1.49% at the rotational speed of 20 r/min. The maximum coefficient of variation of the fertilization stability was 2.86% at the rotational speed of 40 r/min, while the average fertilizer amount per lap for each distributor was 26.25 g/r. The results of the dynamic fertilization tests showed that the maximum relative error of the fertilizer distribution amount was 2.00% when the target fertilizer rates were 20, 30, and 40 kg/667 m2. The results of the field tests showed that the average relative error of the fertilization amount was 3.53%, which satisfies the design standard. This research provides a reference for optimizing pneumatic fertilizer delivery systems and improving fertilization control systems and other pneumatic precision fertilizer application devices.Keywords: agricultural machinery, deep precision fertilization, pneumatic, variable rate, transplanter, vibration eliminationDOI: 10.25165/j.ijabe.20201306.5479Citation: Zha X T, Zhang G Z, Zhang S J, Hou Q X, Wang Y, Zhou Y. Design and experiment of centralized pneumatic deep precision fertilization device for rice transplanter. Int J Agric & Biol Eng, 2020; 13(6): 109–117.